Modification of Neurogenic Colonic Motor Behaviours by Chemogenetic Ablation of Calretinin Neurons - Feng, Jing; Hibberd, Tim J.; Luo, Jialie; Yang, Pu; Xie, Zili; Travis, Lee; Spencer, Nick J.; Hu, Hongzhen (Frontiers in Cellular Neuroscience, 2022)
How the enteric nervous system determines the pacing and propagation direction of neurogenic contractions along the colon remains largely unknown. We used a chemogenetic strategy to ablate enteric neurons expressing calretinin (CAL). Mice expressing human diphtheria toxin receptor (DTR) in CAL neurons were generated by cross breeding CAL-ires-Cre mice with Cre-dependent ROSA26-DTR mice. Immunohistochemical analysis revealed treatment with diphtheria toxin incurred a 42% reduction in counts of Hu-expressing colonic myenteric neurons (P = 0.036), and 57% loss of CAL neurons (comprising ~25% of all Hu neurons; P = 0.004) compared to control. As proportions of Hu-expressing neurons, CAL neurons that contained nitric oxide synthase (NOS) were relatively spared (control: 15±2 %, CAL-DTR: 13±1 %; P = 0.145), while calretinin neurons lacking NOS were significantly reduced (control: 26±2 %, CAL-DTR: 18±5 %; P = 0.010). Colonic length and pellet sizes were significantly reduced without overt inflammation or changes in ganglionic density. Interestingly, colonic motor complexes (CMCs) persisted with increased frequency (mid-colon interval 111±19 vs 189±24 seconds, CAL-DTR vs control, respectively, P < 0.001), decreased contraction size (mid-colon AUC 26±24 vs 59±13 gram.seconds, CAL-DTR vs control, respectively, P < 0.001), and lacked preferential anterograde migration (P < 0.001). The functional effects of modest calretinin neuron ablation, particularly increased neurogenic motor activity frequencies, differ from models that incur general enteric neuron loss, and suggest calretinin neurons may contribute to pacing, force, and polarity of CMCs in the large bowel.